Analisis Faktor-Faktor yang Mempengaruhi Loyalitas Pelanggan Padan NAEM 555 CUCIAN: Nor Asmi, Mardatillah - mardatillah mardatillah (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2021)
This research aims to study and analyze the factors that influence customer loyalty at Naem 555 Laundry. This type of research is quantitative descriptive by using a sample of 103 people. The results of this study indicate that simultaneous variables of satisfaction, emotional bonding, trust, choice reduction and habit and history with company simultaneously have a significant effect to customer loyalty. Partially, satisfaction, trust, and choice reduction and habit variables have a significant effect on customer loyalty while the partial variables of emotional bonding and history with company are not significant to customer loyalty. The variable that has the most dominant influence on customer loyalty is the satisfaction variable.